The pursuit of history : aims, methods and new directions in the study of history - Tosh, John. (London : Routledge/Taylor & Francis Group, 2015)
"This classic introduction to the study of history invites the reade r to stand back and consider some of its most fundamental questions: Wh at is the point of studying history? How do we know about the past? Doe s an objective historical truth exist and can we ever access it? In ans wering these central questions, John Tosh argues that, despite the impr ession of fragmentation created by postmodernism in recent years, histo ry is a coherent discipline which still bears the imprint of its ninete enth-century origins. Consistently clear-sighted, he provides a lively and compelling guide to a complex and sometimes controversial subject, while making his readers vividly aware of just how far our historical k nowledge is conditioned by the character of the sources and the methods of the historians who work on them. The sixth edition has been substan tially revised and updated throughout. New for this edition are: a bran d new chapter on public history; sections on digitised sources and hist orical controversy; discussion of topics including transnational histor y and the nature of the archive; an expanded range of examples and case studies; a comprehensive companion website providing valuable supporti ng material, study questions and suggestions for further reading. Lucid and engaging, this edition retains all the user-friendly features that have helped to make this book a favourite with both students and lectu rers, including marginal glosses, illustrations, suggested further read ing and boxed guides to key events and people. Along with its companion website, this is an essential guide to the theory and practice of hist ory"--Provided by publisher.
"Discusses historiography and the theory and practice of history. Su pplemented by illustrations, marginal glosses and suggestions for furth er reading"--Provided by the publisher.
Historical awareness -- The uses of history -- Mapping the field -- The raw materials -- Using the sources -- Writing and interpretation -- The limits of historical knowledge -- History and social theory -- Cul tural evidence and the cultural turn -- Gender history and postcolonial history -- Memory and the spoken word -- History beyond academia.
Includes bibliographical references and index.
Keywords: Historiography; History -- Philosophy; Historiography -- Philosophy; History -- Methodology; Historiography -- Methodology; Great Britain -- Historiography